Early Epinephrine Improves the Stabilization of Initial Post-resuscitation Hemodynamics in Children With Non-shockable Out-of-Hospital Cardiac Arrest - Lin, Yan-Ren; Li, Chao-Jui; Huang, Cheng-Chieh; Lee, Tsung-Han; Chen, Tren-Yi; Yang, Mei-Chueh; Chou, Chu-Chung; Chang, Chin-Fu; Huang, Hsi-Wen; Hsu, Hsiu-Ying; Chen, Wen-Liang (Frontiers in Pediatrics, 2019)
Background: In children with non-shockable out-of-hospital cardiac arrest, early epinephrine (EE) might help to establish the return of spontaneous circulation (ROSC) and be associated with survival. In the present study, we aimed to analyse the effects of EE on outcomes and post-resuscitation haemodynamics in children with non-shockable OHCA. Methods: This was a retrospective analysis of data from 216 children (< 19 years) who had suffered non-traumatic and non-shockable OHCA and received epinephrine for resuscitation (Jan 1, 2006–Dec 31, 2014). Demographics, pre-/in-hospital information, and the time to the first dose of epinephrine were recorded. Early post-resuscitation haemodynamics (the first hour after sustained ROSC), survival and good neurological outcomes (Pediatric Cerebral Performance Category Scales 1 or 2) were analysed by the time to epinephrine – classified as early (EE): <15 min, intermediate (IE): 15-30 min, or late (LE): >30 min. Results: Twenty-eight (13.0%) children survived to discharge, but only 17 (7.9%) had good neurological outcomes. In all, 41 (18.9%) children received EE; in comparison to IE and LE, this was significantly associated with tachycardia (73.9%) in the post-resuscitation period (p<0.05). Tachycardia (OR: 7.41, 95% CI: 1.96-29.31) and hypertension (OR: 6.03, 95% CI: 1.85-13.77) were significantly associated with EE after adjusting for confounding factors. EE was also significantly associated with better overall outcomes than ME and LE (any ROSC, sustained ROSC, survival to the intensive care unit, admission, survival to discharge and good neurological outcomes, all p<0.05) Conclusions: EE helped to establish ROSC, but was also associated with more tachycardia and hypertension in the early post-resuscitation period. In children with non-traumatic and non-shockable OHCA, EE was associated with a higher survival rate and better neurological outcomes than were ME and LE.